Perubahan Pengeluaran Konsumsi Masyarakat Kabupaten Barito Kuala Selama Masa Pandemi Covid-19 dengan Growth Incidence Curve - Igarta, Kisfendie Regga Rahmad; Tanur, Erwin (Ecoplan, 2023)
The COVID-19 pandemic that hit the world in early 2020 caused economic shock in Barito Kuala Regency. According to Statistics Indonesia of Barito Kuala Regency, the economy of Barito Kuala Regency in 2020 turned minus by 1.06 percent. This economic shock had an impact on consumption expenditure in all segments of households, including the poor. This study aims to determine changes in consumption expenditure in all percentiles of per capita expenditure in Indonesia. It used the Socio-Economic National Survey held by Statistics Indonesia. The Growth Incidence Curve (GIC) was employed, including in urban and rural areas, during and after the pandemic. In this research, the period of 2020-2021 was used to describe “during the pandemic”. The results indicated that, at this time, the consumption expenditure of the poor could be maintained with various social safety programs. Even for the urban areas, consumption expenditure increased across all percentiles. Meanwhile, 2021-2022 was used to describe “after the pandemic”. Interestingly, the consumption expenditure, during this period, was actually still under pressure. One of the possible reasons might be regarding the existence of social safety programs. When the pandemic began decreasing, the safety program was no longer provided massively like during the pandemic.